Tajikistan’s agrifood system structure and drivers of transformation - Diao, Xinshen; Fang, Peixun; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Akramov, Kamiljon T.; Ellis, Mia (International Food Policy Research Institute, 2023)
Tajikistan experienced strong annual economic growth of 6.8 percent during the 2011 to 2020 period (TAJSTAT 2020). This has translated into improved living standards, with the national poverty rate falling from 53.1 percent in 2007 to 26.3 percent in 2019 (World Bank 2023a). The global COVID-19 pandemic caused a significant slowdown in economic growth in 2020, but the economy rebounded in 2021. However, as a country heavily reliant on wheat and fuel imports, Tajikistan was severely affected by the Russia-Ukraine war that started in 2022, and more recently by the global recession in 2023 (Arndt et al. 2023; Diao and Thurlow 2023). Private remittances are the largest source of foreign exchange, accounting for nearly one-third of Tajikistan’s GDP and more than 40 percent of total foreign inflows. Russia is the most important destination for Tajikistan’s emigrants working abroad, and the ongoing war will continue to affect movement of people and inflows of remittances. Tajikistan’s GDP growth is projected to be 6.5 percent in 2023 and 5.0 percent in 2024 (World Bank 2023b), below its pre-pandemic growth trajectory.